Unraveling the Near-Unity Narrow-Band Green Emission in Zero-Dimensional Mn2+-Based Metal Halides: A Case Study of (C10H16N)2Zn1-xMnxBr4 Solid Solutions - Zhou, Guojun; Liu, Zhiyang; Huang, Jinglong; Molokeev, Maxim S; Xiao, Zewen; Ma, Chonggeng; Xia, Zhiguo (The journal of physical chemistry letters, 2020)
Zero-dimensional (0D) Mn2+-based metal halides are potential candidates as narrow-band green emitters, and thus it is critical to provide a structural understanding of the photophysical process. Herein, we propose that a sufficiently long Mn-Mn distance in 0D metal halides enables all Mn2+ centers to emit spontaneously, thereby leading to near-unity photoluminescence quantum yield. Taking lead-free (C10H16N)2Zn1-xMnxBr4 (x = 0-1) solid solution as an example, the Zn/Mn alloying inhibits the concentration quenching that is caused by the energy transfer of Mn2+. (C10H16N)2MnBr4 exhibits highly thermal stable luminescence even up to 150 °C with a narrow-band green emission at 518 nm and a full width at half maximum of 46 nm. The fabricated white light-emitting diode device shows a high luminous efficacy of 120 lm/W and a wide color gamut of 104% National Television System Committee standard, suggesting its potential for liquid crystal displays backlighting. These results provide a guidance for designing new narrow-band green emitters in Mn2+-based metal halides.Zero-dimensional (0D) Mn2+-based metal halides are potential candidates as narrow-band green emitters, and thus it is critical to provide a structural understanding of the photophysical process. Herein, we propose that a sufficiently long Mn-Mn distance in 0D metal halides enables all Mn2+ centers to emit spontaneously, thereby leading to near-unity photoluminescence quantum yield. Taking lead-free (C10H16N)2Zn1-xMnxBr4 (x = 0-1) solid solution as an example, the Zn/Mn alloying inhibits the concentration quenching that is caused by the energy transfer of Mn2+. (C10H16N)2MnBr4 exhibits highly thermal stable luminescence even up to 150 °C with a narrow-band green emission at 518 nm and a full width at half maximum of 46 nm. The fabricated white light-emitting diode device shows a high luminous efficacy of 120 lm/W and a wide color gamut of 104% National Television System Committee standard, suggesting its potential for liquid crystal displays backlighting. These results provide a guidance for designing new narrow-band green emitters in Mn2+-based metal halides.